2018
DOI: 10.3390/w10081101
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Irrigation Canal System Characteristics in Heilongjiang Province and the Influence on Irrigation Water Use Efficiency

Abstract: Irrigation water use efficiency is a primary evaluation index that links economic production development with the efficient use of water resources. Canal water conveyance is an important part of irrigation, and the distribution characteristics of canal systems have an important influence on irrigation water use efficiency. In this paper, 75 irrigated districts in Heilongjiang Province in 2015 were selected as the study objects. The main, branch, lateral, and sublateral canals were graded into first-, second-, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 28 publications
1
1
0
Order By: Relevance
“…The result is in line with [43][44][45]51,55,56]. The negative coefficient of the education variable probably indicated that farmers tend to overuse production inputs, resulting in a production decrease, as well as a decrease in technical efficiency [57]. In contrast, other researchers showed that technical efficiency will increase, as well as farmers' education [42,44,54].…”
Section: Analytical Resultssupporting
confidence: 58%
“…The result is in line with [43][44][45]51,55,56]. The negative coefficient of the education variable probably indicated that farmers tend to overuse production inputs, resulting in a production decrease, as well as a decrease in technical efficiency [57]. In contrast, other researchers showed that technical efficiency will increase, as well as farmers' education [42,44,54].…”
Section: Analytical Resultssupporting
confidence: 58%
“…Since 1979, the International Commission on Irrigation and Drainage (ICID), the American Society of Civil Engineers (ASCE), the Food and Agriculture Organization of the United Nations (FAO) and the Irrigation Association of Australia (IAA) have put forward the definition of irrigation efficiency successively [23][24][25][26][27]. Other evaluation indicators, such as the canal WUE and the field WUE, can also be used to represent agricultural WUE [28,29]. Cao et al established the generalized efficiency (GE) to assess the effective use rate of generalized water resources, and this index was defined as the ratio of total water consumption to total water resources [20].…”
Section: Introductionmentioning
confidence: 99%